Does Collaborative Governance Work? A longitudinal, case-based study of how local governments adapt to collaborative governance, and with what effect. - McQuaid, Siobhan (Trinity College Dublin. School of Business. Discipline of Business & Administrative Studies, 2024)
This study asks how do local governments implement and adapt to the collaborative governance arrangements required for nature-based solutions (NBS) and does collaborative governance work? A longitudinal, comparative case study methodology was applied to study three local governments in Genk (Belgium), Glasgow (Scotland) and Poznan (Poland) over 5 years as they implemented collaborative governance regimes (CGRs) to deliver NBS addressing complex local challenges. The Emerson et al. Framework for Integrative Governance (2012) and Emerson and Nabatchi’s Typology of CGRs (2015a) were applied to answer the first research question. Emerson and Nabatchi’s Productivity Performance Matrix (2015b) was applied to answer the second research question. The Emerson et al. Framework for Integrative Governance (2012) was found to be highly relevant to understanding the contextual conditions influencing the formation and dynamics of CGRs in case study cities. Public resource conditions, socio-economic characteristics, previous history of engagement, policy and legal frameworks were seen to be highly relevant contextual factors. The main driver to formation of a CGR in all three cities was the incentive of grant funding. Collaboration to secure financing remained an important driver over the study period. In all three cities, the physical and spatial dimension of nature-based solutions was also seen to be a direct driver of collaboration. A limitation of the framework was the lack of attention given to barriers to collaboration. The Covid pandemic, public management models and cultures were found to be significant constraints. Emerson and Nabatchi’s Typology of CGRs (2015a) was found to be of limited usefulness in characterising the conditions and characteristics of formation of CGRs in case study cities. In contrast, Emerson and Nabatchi’s guidance on collaboration dynamics (2015a) was found to be highly insightful in comparing the unfolding of collaboration processes in cities. Intra-organisational challenges relating to public administration silos were evident in developing procedural and institutional arrangements for collaborative governance. Measures to support the transition from city-led governance to community co-governance were observed. A limitation however was the limited treatment of legitimacy and guidance on collaborative actions. Collaboration actions were seen to be split between process actions (58%) related to overall CGR activities and productivity actions (42%) related to achieving specific NBS target goals. Emerson and Nabatchi’s Productivity Performance Matrix (2015) provided insightful guidance on performance. Local governments reported improved governance structures and processes for managing complex, boundary-spanning projects, the emergence of new innovations facilitating multi-stakeholder engagement on social innovation and better access to shared knowledge and resources. At the level of the CGR, external legitimacy and recognition were found to be of critical importance in securing funding and resources to ensure the ongoing viability of CGR activities. In relation to the target goal of NBS implementation, Poznan had fully implemented city-wide NBS at the end of the study period, measuring clear environmental and social benefits. However, they failed to secure high level legitimacy and funding to continue CGR activities. Glasgow and Genk reported good intermediate socio-economic results. They achieved high-level legitimacy securing resources and support for ongoing activities. In all three cities, a proliferation of `mini-CGR’ type arrangements were seen to emerge adding complexity to long term governance arrangements. In conclusion, this study found that collaborative governance worked for the implementation of NBS and generated many benefits for local government organisations. However good outcomes on the ground were insufficient to ensure long term viability. Other contextual factors, from public management cultures to political and financial challenges were seen to impact on long term sustainability. The most significant contributions to theory from this research are firstly, an adapted version of the Emerson and Nabatchi framework to address key limitations and secondly, proposed revisions of the performance dimensions of the Productivity Performance Matrix.
APPROVED
Keywords: Collaborative Governance; Local government; Public sector management models; Sustainability; Nature-Based Solutions (NbS)